Ferric nitrilotriacetete augments 7,12-dimethylbenz(A) anthraceneinitiated and croton oil-promoted skin carcinogenesis - Hassan Rezazadeh; Mohammad Ramazani; Ahad Bavili-Tabrizi; Siavoush Dastmalchi; Alireza Mohajjel Nayebi; Armin Taheri; Rana Eftekharnahli; Senty Vun-Sang; Mohammad Iqbal (Malaysian Society for Biochemistry & Molecular Biology (MSBMB), 2025)
Although Ferric nitrilotriacetate (Fe-NTA) is a known renal carcinogen, its carcinogenic potential in skin remains poorly understood. This study aims to investigate the potential augmentation effects of Fe-NTA on the initiation and promotion stages of DMBA-induced and croton oil-promoted skin cancer development, shedding light on the mechanisms underlying the synergistic carcinogenic action of these agents. We for the first time demonstrates that Fe-NTA enhances skin carcinogenesis in mice initiated by 7,12-dimethylbenz(a)anthracene (DMBA) and promoted by croton oil. This study looked at the impact of Fe-NTA on croton oil-promoted tumour activation in 7,12-dimethylbenz(a)anthracene (DMBA)-initiated mouse cutaneous carcinogenesis. Four groups of mice, each consisting of 20 animals, were selected for the carcinogenicity tests. Group I served as the control and received no treatment. Groups II, III, and IV received daily topical applications of Fe-NTA at doses of 6, 9, and 12 mg iron per mouse, respectively, for a period of 2 weeks. Nine hours after the last administration of Fe-NTA, all groups of mice, including the control group, received a single topical application of 60 μg of DMBA in 200 μl of acetone. One week after DMBA treatment, the mice received twice-weekly topical applications of 1 mg croton oil in 200 µl acetone/mouse for a period of 30 weeks. The mice were then monitored for the occurrence of tumors up to 36 weeks. Higher doses of Fe-NTA induced an increase in tumor occurrence over times as compared to the control (DMBA+ Croton oil) treated group. Tumors appeared earlier in the Fe-NTA group, with a higher incidence number of tumors. We propose that Fe-NTA boosts croton oil, tumor-promoting potential, and that Fe-NTA-induced oxidative stress is effective for croton-oil mediated cutaneous carcinogenesis. In addition, croton oil-mediated lipid peroxide induction and [3H] thymidine uptake was greater in Fe-NTA treated group. We propose that Fe-NTA increases tumor promotion capability of croton oil and oxidative stress induced by Fe-NTA is effective for croton oil mediated cutaneous tumorigenesis.